A virtual reality role-playing serious game for experiential learning. Issue 5 (19th May 2022) - Alrehaili, Enas Abdulrahman; Al Osman, Hussein
ABSTRACT: Educational systems can benefit from Virtual Reality's (VR) ability to support experiential learning. In particular, VR based games, especially role-playing serious games (RPGs), can promote learning through the simulation of various educational scenarios. This study proposes an immersive VR-RPG to educate players about the behavior of honeybees. The player adopts the role of a honeybee and experiences a virtual world mimicking the real one from the honeybee's perspective. Unlike most studies in educational VR, we assess the impact of immersion on knowledge gain by testing the players' knowledge on the subject before, immediately after, and one week following the use of the system. We also compare the proposed system with both a conventional and a desktop VR-RPG approach. The results indicate that students significantly gained knowledge in all methods compared to the pre-test. We found that the immersion level for both tested VR-RPGs did not have a significant effect on learning. However, the study showed an improvement in knowledge retention for the desktop VR-RPG users compared to those of the conventional method. Moreover, the results revealed that users of the immersive and desktop VR-RPGs were more motivated and engaged compared to those of the conventional method.